The Effect of Career Development on Employee Performance at PT Angkasa Pura Solusi - Siti Azizah Hamidah; Ratna Dewi; Vivi Liana; Sewaka Sewaka (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This research is motivated by a decrease in work productivity in Indonesia, which impacts employee performance. One of the company’s efforts to increase employee productivity and performance is employee career development through training activities. Through employee career development, employee knowledge, abilities, and skills will increase and impact employee productivity and performance. This study aims to determine the effect of career development on employee performance. The population is the total number of objects of a study. The population in this study were employees of PT Angkasa Pura Solusi Soekarno-Hatta International Airport Terminal 3 Domestic, 4th Floor Office Building, Tangerang, amounting to 99 people. At the same time, the sample in this study was 80 people—data analysis technique using simple linear regression analysis. The results showed a positive influence between career development and employee performance when viewed from the t-test with a value of tcount > table (7.185 > 1.988) with a significant level of 0.05. Based on the analysis of the coefficient of determination, it can be seen that the R Square value of 0.398 or 39.8% of employee performance variables can be explained by career development variables. In comparison, the remaining 60.2% is influenced by other variables not explained by the author in this study. The results showed a positive influence between career development and employee performance when viewed from the t-test with a value of t-count > t-table (7.185 > 1.988) with a significant level of 0.05. Based on the analysis of the coefficient of determination, it can be seen that the R Square value of 0.398 or 39.8% of employee performance variables can be explained by career development variables. In comparison, the remaining 60.2% is influenced by other variables not explained by the author in this study. The results showed a positive influence between career development and employee performance when viewed from the t-test with a value of t-count > t-table (7.185 > 1.988) with a significant level of 0.05. Based on the analysis of the coefficient of determination, it can be seen that the R Square value of 0.398 or 39.8% of employee performance variables can be explained by career development variables. In comparison, the remaining 60.2% is influenced by other variables not explained by the author in this study.